REAL-TIME LEARNING ANALYTICS: THE ROLE OF AI IN MONITORING STUDENT PROGRESS - Marten Mahadjani; Li Wei; Liu Yang (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
The integration of Artificial Intelligence (AI) in education has significantly transformed how student progress is monitored in real-time, offering valuable insights into individual learning trajectories. Real-time learning analytics powered by AI provide educators with the ability to track and assess students’ performance continuously, facilitating timely interventions and personalized learning experiences. Despite the potential of AI to enhance educational outcomes, its impact on the overall teacher-student dynamic and the challenges associated with its integration into traditional pedagogical frameworks remain underexplored. This study aims to investigate the role of AI in real-time learning analytics and its effect on monitoring student progress, exploring both its benefits and limitations. The research employs a mixed-methods approach, combining quantitative surveys, qualitative interviews, and classroom observations across 10 educational institutions utilizing AI-powered learning tools. The results indicate that AI tools significantly improve student engagement, performance, and the timeliness of feedback, but concerns about the depersonalization of interactions were also raised by both students and teachers. The study concludes that while AI can enhance the monitoring of student progress, it must be integrated in a way that preserves the human aspects of teaching. AI should complement, not replace, the teacher's role in providing emotional and social support in the learning process.